2016
DOI: 10.1098/rspb.2016.0812
|View full text |Cite
|
Sign up to set email alerts
|

Marine Phytophthora species can hamper conservation and restoration of vegetated coastal ecosystems

Abstract: Phytophthora species are potent pathogens that can devastate terrestrial plants, causing billions of dollars of damage yearly to agricultural crops and harming fragile ecosystems worldwide. Yet, virtually nothing is known about the distribution and pathogenicity of their marine relatives. This is surprising, as marine plants form vital habitats in coastal zones worldwide (i.e. mangrove forests, salt marshes, seagrass beds), and disease may be an important bottleneck for the conservation and restora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 66 publications
2
69
0
Order By: Relevance
“…nitida has been described. In addition, a sediment layer might also have additional effects such as preventing the development of marine phytophthora species [58]. …”
Section: Discussionmentioning
confidence: 99%
“…nitida has been described. In addition, a sediment layer might also have additional effects such as preventing the development of marine phytophthora species [58]. …”
Section: Discussionmentioning
confidence: 99%
“…port infrastructure development and dredging) and natural disturbances (e.g. disease and storms) (Cambridge & McComb, 1984; Short & Burdick, 1996; Wyllie-Echeverria & Ackerman, 2003; Kim et al, 2015; Macreadie et al, 2015; Zhang et al, 2014; Lin et al, 2016; Govers et al, 2016). These issues have led to the recent development of restoration efforts to compensate or mitigate seagrass losses, and to enhance the associated ecosystem services (Shafer & Bergstrom, 2010; Suykerbuyk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Numerous new species were recently isolated from forests, streams and irrigation water but their pathogenicity have not been determined. Although Phytophthora species are well known for causing diseases of terrestrial plants, Govers et al,20 reported recently the widespread infection of a common seagrass species, Zostera marina (eelgrass) across the northern Atlantic and Mediterranean by P. gemini Man in't Velf, K. Rosend, Brouwe & de Cock, P. inundata Brasier, Sánch, Hern & Kirk and an unidentified species of Phytophthora threatening the conservation and restoration of vegetated marine coastal systems. The taxonomy of Phytophthora species has been traditionally based on morphological characters, e.g.…”
Section: Phytophthoramentioning
confidence: 99%